Is leader proactivity enough: Importance of leader competency in shaping team role breadth efficacy and proactive performance - Chiu, C.Y.; Wu, C.H.; Bartram, A.; Parker, Sharon; Lee, C. (2023)
The present study is designed to investigate how leader proactive personality and competency jointly relate to team proactivity. Drawing on social cognitive theory, we hypothesize that proactive yet incompetent leaders diminish the magnitude and enhance the dispersion of team role breadth efficacy, defined as the collective confidence to engage in a range of integrative, interpersonal, and proactive tasks, which lowers team proactive performance. The test of the hypotheses, based on two waves of surveys of members of 66 professional work teams and their leaders, reveals three main findings. First, leaders' proactive personality is negatively associated with the magnitude and positively related to the dispersion of team role breadth efficacy when their competency is low. Second, proactive personality is positively associated with the magnitude, but not the dispersion, of team role breadth efficacy if their competency is high. Third, the leader proactivity-competency interactive effect relates positively to team proactive performance, through the mediation of the optimal configuration of team role breadth efficacy (high magnitude + low dispersion). This study thus highlights the need to consider both proactive personality and competency for team management and their implications for leaders' own career success.